Effect of Qing'e Formula on OPN, BSP and Integrin ɑvβ3Expression in Bone Tissue of Ovariectomized Rats - Yuqing SUN; Wenjuan LUO; Bingqi WANG; Xiang CHEN; Xiaokang JIA; Yanping LIN (康复学报)
Objective:To investigate the effect of Qing'e formula on OPN, BSP and Integrin ɑvβ3expression in bone tissue of ovariectomized rats, and further explore the prevention and therapeutic mechanism of Qing'e formula in osteoporosis of postmenopausal.Methods:120 of three-months old female SD rats were randomly divided into saline group, Qing'e formula group, Gushukang group and sham-operated group with 30 rats in each group. All rats except the sham-operated group were ovariectomized and marked as OVX groups. Three days after operation, the rats were fed daily with normal saline (the sham-operated group, the saline group), Qing'e formula (the Qing'e formula group) and Gushukang (the Gushukang group), respectively. Ten rats were randomly chosen from each group, and sacrificed on week 4, 8 and 12, after treatment. The serum TRACP5b were measured by ELISA. The bone tissues from the left proximal shin were sectioned and processed HE staining. The bone mineral densities (BMD) were measured by dual-energy X-ray absorptiometry (DXA) for the 3-5 lumbar vertebra. The expressions of OPN, BSP, Itgɑvβ3mRNA and protein were measured by quantitative PCR (Q-PCR) and Western Blot, respectively.Results:The BMD and the area percentage of trabecular of the OVX groups were lower compared with the sham-operated group, of which the saline group were the lowest in week 8 and week 12 (P<0.05 or P<0.01). The BMD of the Qing'e formula group were higher than that of the saline group in week 12 (P<0.01). The area percentage of trabecular of the Qing'e formula group were higher than that of the saline group in week 8 and week 12 (P<0.05). The expression levels of OPN, BSP, Itgɑv, Itgβ3mRNA and protein along with serum TRACP5b of the OVX groups were higher than the sham-operated group in 4, 8 and 12 weeks, and the saline group showed the highest expression (P<0.01). Except the serum TRACP5b in week 12, the expression mentioned above of the Qing'e formula group was lower than that of the saline group (P<0.05 or P<0.01).Conclution:Ovariectomy promotes the expression of OPN, BSP, Itgɑv, Itgβ3 which enhance the function of osteoclast, and lead to the occurrence of osteoporosis. The Qing'e formula can suppress osteoclastic bone resorption by reducing the expression of bone tissue OPN, BSP and its receptor Itgɑv, Itgβ3. Qing'e formula plays a positive role in postmenopausal osteoporosis prevention and therapy.